(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This research paper delves into the significance and application of tenses in the English language. Tenses are fundamental to constructing clear and accurate sentences, allowing speakers and writers to convey when actions occur. This paper categorizes the tenses into three main groups—past, present, and future—and discusses their various forms and contextual applications. Through examples and analysis, this work highlights common misconceptions and the importance of mastering tense usage for effective communication.